TEOLOGI PASTORAL DALAM KEUNIKAN KONTEKS INDONESIA - Agnes Beatrix Jackline Raintung; Chaysi Tiffany Raintung (POIMEN Jurnal Pastoral Konseling, 2020)
ABSTRACT The notion that pastoral theology is less intellectual than biblical, systematic and historical theology is also considered only as applied theology makes theology often overlooked. Efforts to make pastoral theology a branch of theology parallel to each other, require a long struggle by European and American pastoral theologians. The long struggle that produced positive results also felt its impact in the development of pastoral theology in Indonesia. However, the concept of pastoral theology developed in the Western world and then brought to Indonesia influenced the concept of Indonesian pastoral theology. The style and color of Western pastoral theology is still very thick, because it needs to be contextualized according to the conditions of Indonesian society. Western pastoral theology is thick with its individualism, while the Indonesian context is very diverse. For Indonesia with the context of its plural society with all its unique contexts and problems, pastoral theology is a theological reflection on and in the context of pastoral care. The correlative theology method is seen as a theological method that is relevant to the Indonesian context.